Georgia : Technical Assistance Report-Strengthening Regulation, Supervision, and Oversight of Micro Lending Institutions. (IMF Staff Country Reports; Country Report, 2020)
In the past two years, the NBG has adopted a series of measures to strengthen nonbank sector financial regulation, supervision, and oversight.1 The MCM TA mission in 2017 provided recommendations along these lines, most of which have been implemented by the NBG. Currently, the nonbank sector consists of Micro Financial Institutions (MFIs) and Loan Issuing Entities (LIEs). In reforming the sector, the NBG has, among others: (i) amended laws and issued new and revised regulations on registration, capital, and liquidity requirements for MFIs; (ii) significantly expanded supervisory powers and authorities and increased supervisory resources for the nonbank sector; (iii) registered 200 LIEs; and (iv) put in place consumer protection and responsibility lending rules. These new measures have helped to enhance the resilience of the nonbank sector, weed out those that are non-viable, and improved the reputation of the MFI brand.